2021
DOI: 10.1186/s40364-021-00264-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mesothelin CAR T cell therapy for malignant mesothelioma

Abstract: Malignant mesothelioma (MM) is a treatment-resistant tumor originating in the mesothelial lining of the pleura or the abdominal cavity with very limited treatment options. More effective therapeutic approaches are urgently needed to improve the poor prognosis of MM patients. Chimeric Antigen Receptor (CAR) T cell therapy has emerged as a novel potential treatment for this incurable solid tumor. The tumor-associated antigen mesothelin (MSLN) is an attractive target for cell therapy in MM, as this antigen is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 83 publications
1
39
0
Order By: Relevance
“…Earlier reports showing antitumor activity and improved survival in subcutaneous and intraperitoneal preclinical models raised CAR T-cell therapy to a promising treatment modality for those patients (20,21). Furthermore, clinical trials using MSLN-directed CAR T cells have so far demonstrated no on-tumor/off-target toxicity (22)(23)(24)). Yet, phase I studies using MSLN-targeted CAR T cells with murine-derived scFv in patients with solid tumors showed potential but limited effect (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports showing antitumor activity and improved survival in subcutaneous and intraperitoneal preclinical models raised CAR T-cell therapy to a promising treatment modality for those patients (20,21). Furthermore, clinical trials using MSLN-directed CAR T cells have so far demonstrated no on-tumor/off-target toxicity (22)(23)(24)). Yet, phase I studies using MSLN-targeted CAR T cells with murine-derived scFv in patients with solid tumors showed potential but limited effect (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we propose an approach based on dual targeting, split costimulatory signaling and shared CD3ζ chain tailored to target two clinically relevant antigens -GD2 and B7-H3in the disease model of neuroblastoma (NB) [19][20][21] , and further validated the approach with an additional pair of targets, mesothelin (MSLN) and chondroitin sulphate proteoglycan 4 (CSPG4) [22][23][24] . We demonstrated that the designed strategy allows achieving rapid and sustained antitumor effects, which are sustained by optimized signaling, effector molecular signature and metabolic fitness of the CAR-T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Adoptive cell therapy targeting MSLN has emerged as a potential therapy for the treatment of MPM with numerous clinical trials [129]. Chimeric Antigen Receptor (CAR) T cellular immunotherapy entails genetically engineering T cells to target the tumor.…”
Section: Mesothelin-targeted Cellular Therapymentioning
confidence: 99%
“…Overall, the results of MSLN-directed CAR T cell therapy are encouraging, with manageable toxicity and no reported 'on-target/off-tumor' effects. Novel strategies to improve CAR T cell efficacy are currently being tested in clinical trials, with many more in the preclinical stage [129]. Furthermore, allogeneic 'off the shelf' MSLN-targeted CAR T cells are being developed.…”
Section: Mesothelin-targeted Cellular Therapymentioning
confidence: 99%